The vocabulary of the comіс in the operatic works of Vitaliy Hubarenko and Maryna Cherkashyna - Sikorska, Iryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. The creative partnership of V. Hubarenko and M. Cherkashyna holds anoutstanding place in Ukrainian musical theatre. Among their 13 operas, only The Matchmaker by Chance (1982) has undergone several «reincarnations» during Ukraine’s independence. The relevance of it has grown up because of heated debates around the «historically conditioned» Russian-Ukrainian bilingualism. The opera In the Steppes of Ukraine (1987) was never staged, but it consolidated previous techniques, expressive means, musical portraits, and narrative developments, so we can speak about V. Hubarenko’s discourse of comedy in operatic oeuvre. Given that six of his operas were written in collaboration with his wife Marina Cherkashyna (who authored the librettos), — we examine the subject through the lens of the V. Hubarenko – M. Cherkashyna tandem. The main objective of the study. The article aims to see about the vocabulary of the comic in operas of V. Hubarenko and M. Cherkashyna. So our goal was: to examine the contexts of The Matchmaker by Chance and In the Steppes of Ukraine, the history of their composition, their place in Hubarenko’s operatic legacy, traditional and innovative techniques, stylistic features of their genre embodiment, and staging prospects. The methodology The research methodology is based on the following approaches: biographical method — reconstructing factual life events related to the creation of the comic operas of V. Hubarenko and M. Cherkashyna; historical method — contextualizing these works within broader historical and cultural frameworks; structural-functional, genrestylistic, and intonational-dramaturgical analysis — conducting a comprehensive examination of the operas; source studies method — analyzing autographs and archival documents;. Results and conclusions. The Matchmaker by Chance and In the Steppes of Ukraine merge the traditional principles of the Ukrainian lyric-comic genre with modern compositional mentality. A detailed genre-intonational and semantic analysis of both operas reveals the mechanisms by which Hubarenko constructed comic characters. These include : opera symphonization through an extensive leitmotif system; modeling of natural spoken language for characters of different social and emotional backgrounds; folkloric allusions, ranging from direct quotations to stylized adaptations; a diverse genre-intonational palette, incorporating Ukrainian folk (humorous, marching, and fastpaced) songs, European salon dances (waltz, mazurka), Russian sentimental romances, and operatic lexicon. At the same time, Hubarenko managed to integrate all these elements into a unified musical language through his distinctive compositional style. As a result, the operas are perceived as cohesive works and serve as exemplary models of Ukrainian comic opera. Their revival on stage requires both temporal distance and certain textual revisions, considering Ukraine’s historical and political realities.